Evaluation of morphological traits, proline content and antioxidant enzymes activity in chickpea genotypes (Cicer arietinum L.) under drought stress - Parvaneh Abrishamchi; Ali Ganjeali; Hasan Sakeni (پژوهش‌های حبوبات ایران, 2012)
This study aimed to assess the response of chickpea genotypes to drought stress in terms of morphological traits and subsequent biochemical changes to further understanding of drought resistance mechanisms in plants and access to better genetic resources. The chickpea genotypes including MCC776, MCC877, MCC696 and MCC588 evaluated at four soil moisture regimes with field capacity (control), 75%, 50% and 25% of field capacity through a factorial experiment in a completely randomized design with three replications at physiology laboratory in Research Center for Plant Science, during 2009. The results showed that most of the morphological traits such as plant height, shoot and root biomass, total root length and leaf area, were mainly affected by severe drought stress. Moderate drought stress (50% FC moisture and above) had no significant effect on these traits. Reduced soil moisture increased the stem proline content in all genotypes. The highest proline obtained in native genotype candidate (MCC696) at severe drought stress. Enzymes activity of super oxide dismutase and peroxidase increased in drought- sensitive genotype MCC588 than other genotypes. Absence or poor performance of drought tolerance or avoidance mechanisms in MCC588 genotype possibly caused induction of oxidative stress and produced antioxidant enzymes.